If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8 + -18y) + -1(15 + 2y) = 0 Remove parenthesis around (8 + -18y) 8 + -18y + -1(15 + 2y) = 0 8 + -18y + (15 * -1 + 2y * -1) = 0 8 + -18y + (-15 + -2y) = 0 Reorder the terms: 8 + -15 + -18y + -2y = 0 Combine like terms: 8 + -15 = -7 -7 + -18y + -2y = 0 Combine like terms: -18y + -2y = -20y -7 + -20y = 0 Solving -7 + -20y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -20y = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -20y = 0 + 7 -20y = 0 + 7 Combine like terms: 0 + 7 = 7 -20y = 7 Divide each side by '-20'. y = -0.35 Simplifying y = -0.35
| 6x-5=4x+8 | | 0.8x+6=7.2 | | 3a+4=a-18 | | 20/12=12/5 | | 22=2x+6x-10 | | Lx+My=N | | 6=(x/9.6) | | 3x+3=-34 | | Lx+My=Nfory | | 24/48xy•1/6xy | | 8/5a=6 | | 3(3x-5)=10 | | 5m+8=8m-4 | | 24x•1/2y•1/6xy | | -4x^4-3x^2+1=0 | | 6+11x-2=9x+16-4x | | 11=3s-4(27-s) | | -5x-2=15 | | x-0.3x=15.40 | | 1.5(12-3x)=12(1.5-3x) | | 12=e^10r | | 2(14-6x)=8 | | -4x^4-19x^2+5=0 | | f(4)=2+3x | | 92=39(2)+2w | | 42-5x=3x-14 | | 3r-1=r+2 | | 24=12e^10r | | x+0.15x=17.25 | | -28x^2-17x+6=0 | | (5x-10)*(3-x)=0 | | (16-15)q+13=(18-16)q |